Fundos de investimento no Brasil: análise do ponto de equilíbrio de empresas gestoras - Oliveira Filho, Bolivar Godinho de (2001)
This work comprehends relevant aspects of investment funds in Brasil and develops information about investment funds in the United States, which determines the trends of the sector The research was made with seventeen Asset Management Companies in Brasil of several sizes, with the purpose to discover the minimum amount of money necessary to administer a company. The break-even-point analysis demonstrated that there may be several company levels, according to the market segments and cost conformation. The productivity in the companies denotes economic scales in the sector that make the activity an important profit center for the big banks